[OP.LB01.12] CACNA1H MUTATIONS ARE ASSOCIATED WITH YOUNG ONSET AND FAMILIAL FORMS OF PRIMARY ALDOSTERONISM. (September 2016) - Daniil, G.; Fernandes-Rosa, F.L.; Chemin, J.; Jeunemaitre, X.; Polak, M.; Boulkroun, S.; Amar, L.; Strom, T.M.; Lory, P.; Zennaro, M.C.
Abstract : Objective: Primary aldosteronism (PA) is the most common form of secondary hypertension. Mutations in KCNJ5, ATP1A1, ATP2B3 and CACNA1D are found in aldosterone producing adenomas (APA) and familial hyperaldosteronism (FH). Recently, a recurrent germline mutation in CACNA1H (encoding the T-type voltage-dependent calcium channel Cav3.2) was identified in a new familial form of early onset hypertension and PA. Design and method: To identify new genes responsible for PA, we have performed whole exome sequencing in 23 patients with APA, 10 patients with FH and in two trios with the proband presenting early onset PA. Results: We identified four germline CACNA1H variations. p.Ser196Leu and p.Pro2083Leu were found in two patients with FH resembling to FH-II. A p.Val1951Glu variant was identified in a patient with APA, and a de novo p.Met1549Ile variant in a patient showing hypokalemia, hypertension and PA at age 3 months. Electrophysiological analysis of mutant Cav3.2 in HEK293 cells revealed significant changes in the Ca2+ current properties, including slower inactivation (Cav3.21549Ile and Cav3.2196Leu) and a shift in the steady-state inactivation (Cav3.21549Ile, Cav3.2196Leu and Cav3.22083Leu). All mutations (except Cav3.21549Ile) generated an increase in the current facilitation induced by a previous stimulation, very likely increasing the calcium entry via Cav3.2 during sustained activities. Transient transfections of adrenocortical carcinoma H295R-S2 cells showed that, after K+ stimulation, cells overexpressing mutants Cav3.2196Leu and Cav3.21549Ile showed a 2.5-fold (Cav3.2196Leu, p < 0.001) and 4.5-fold (Cav3.21549Ile, p < 0.001) increase in aldosterone biosynthesis compared to wild type Cav3.2. This was associated to an increase in CYP11B2 mRNA levels in cells expressing Cav3.2196Leu (7.5 fold; p < 0.001) and Cav3.21549Ile (3.2-fold; p < 0.001). No difference in aldosterone levels was observed in basal conditions or after Ang2 stimulation. Conclusions: In summary, we identified 4 germline CACNA1H mutations in PA patients with different phenotypic presentations. These mutations induce significant changes in channel properties and are responsible for increased aldosterone production in adrenocortical cells after K+ stimulation. Identification of new CACNA1H mutations that are associated with early onset PA or familial forms diagnosed as FH-II suggests that CACNA1H might be a susceptibility gene predisposing to PA with different phenotypes.